Manajemen Laba, Tata Kelola Perusahaan, Persaingan Pasar Produk Terhadap Perilaku Sticky Cost Di Moderasi Kebijakan Insentif Pajak - Nurul Fithriyyah; Hero Priono (Akuntansi : Jurnal Akuntansi Integratif, 2021)
Abstract This purpose of this study was to determine the effect of earnings management, corporate governance, product market competition on sticky cost behavior by tax incentive policies. This research method uses a quantitative approach. The data collection technique is secondary data of annual financial reports on retail sub-sector companies listed on the Indonesia Stock Exchange for 2016-2020 a total of 28 companies. The samples were determined using purposive sampling. The data analysis method uses moderated regression analysis (MRA). The results of the study are earnings management, corporate governance have a positive and significant effect on sticky cost, and The tax incentive policy is able to moderate the relationship between corporate governance and sticky cost behavior. In this study, it helps to understand the cost behavior of retail sector companies, so it is expected that company management can more accurately estimate the value of the company in the future. The next research is expected to use a qualitative approach to expand studies related to research linking sticky cost behavior.